2018
DOI: 10.1016/j.jgr.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic acids and heat treatment on ginsenoside conversion

Abstract: BackgroundHeat treatments are applied to ginseng products in order to improve physiological activities through the conversion of ginsenosides, which are key bioactive components. During heat treatment, organic acids can affect ginsenoside conversion. Therefore, the influence of organic acids during heat treatment should be considered.MethodsRaw ginseng, crude saponin, and ginsenoside Rb1 standard with different organic acids were treated at 130°C, and the chemical components, including ginsenosides and organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…(2011) and Jang et al. (2018) suggested that organic acids in combination with heat treatment be used to improve bioactive components through the conversion of major ginsenosides to minor ginsenosides, which was also observed in this study (Tables 3 and 6), where immersion in acidic FTL and steam treatment were applied.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…(2011) and Jang et al. (2018) suggested that organic acids in combination with heat treatment be used to improve bioactive components through the conversion of major ginsenosides to minor ginsenosides, which was also observed in this study (Tables 3 and 6), where immersion in acidic FTL and steam treatment were applied.…”
Section: Resultssupporting
confidence: 80%
“…Several researchers have attempted to enhance ginsenosides in Korean ginseng using organic acids and heat treatment. They reported that organic acids such as acetic acid, ascorbic acid, citric acid, malic acid, lactic acid, and oxalic acid could convert neutral ginsenosides to rare ginsenosides, resulting in improved functionality of ginseng, hence increasing its value (Jang et al., 2018; Kim et al., 2010; Liu et al., 2016; Yi et al., 2010). After heat treatment, the major ginsenosides could be converted to low‐polar ginsenosides such as Rg2, Rg6, F4, Rk3, and Rg5 by hydrolysing the sugar chains (Kim et al., 2013; Zhang et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous report, the Rb1/Rg1 ratio in PG is usually between 1 and 3, while Rb1/Rg1 values of approximately 10 or greater are characteristic of AG [ 29 ]. With the popularity of mass spectrometry, some trace markers such as Rf, p-F11 and Rs1 can also be used for differentiating PG from PQ [ 30 ]. Notoginsenoside R1 was only observed in NG.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also found that treatment of ginsenosides Rh1, Rh2, and Rg3 with 0.01% formic acid at 120 °C for 4 h resulted in the formation of ginsenosides Rk3 and Rh4, Rk1 and Rg5, and Rk2 and Rh3, respectively [ 93 ]. In addition, through acid hydrolysis, an addition reaction, and dehydration, formic acid promotes the transformation from ginsenosides Re, Rf, and Rg2 into several minor ginsenosides, i.e., F1, Rh1, Rf2, Rf3, Rg6, F4, and Rg9 [ 94 , 95 ]. Besides citric acid and formic acid, other acids, such as acetic acid, ascorbic acid, and lactic acid, can also be used in the chemical transformation of major ginsenosides into minor ginsenosides in ginseng samples [ 96 , 97 ].…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%